Tác động của cạnh tranh ngân hàng đến tài chính toàn diện: Nghiên cứu tại Việt Nam - Tram Thi Xuan , Huong; Nguyen Tu , Nhu; Cao Ngoc , Thuy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
By using the regression method for panel data, the study focuses on measuring the impact of banking competition on the development of financial inclusion (FI) in Vietnam from 2006 to 2018. The reliable research result shows that banking competition has a positive effect on FI. This is also a piece of important empirical evidence for bank managers and policymakers. Therefore, the study proposes appropriate solutions not only to help banks to build competitive strategies but also to contribute to the development plan of FI in Vietnam.
Keywords: Competition; Commercial bank; Finance inclusion; Vietnam